Social protection and resilience during COVID-19: An interdisciplinary analysis of the role of informal worker associations in Kenya - Cille Melin Gundertofte; Gustav Eik Thur; Nina Torm (Roskilde University, Department of Social Sciences and Business, Socio-Economic Research Centre (SECO), 2022)
This paper examines how different theoretical perspectives on resilience can be combined and applied to investigate Kenyan informal worker associations (IWAs) as social protection providers during COVID-19. We develop a model which shows that resilience is a dynamic property that can be affected by the interplay between actors in and across system-levels. The model employs the concepts of antecedent and ongoing states during crises, four cornerstones of resilience, and three resilience capacities: absorptive, adaptive, and transformative capacity. In combination, this leads us to introduce 'environmental enablers and disablers' as a tool to explain the implications systems can have on the resilience of other systems. The analytical framework is applied to the case of Kenyan IWAs representing three sectors (construction, trade and transport) which vary substantially in the measures adopted during COVID-19. We find that the 'environmental enablers and disablers tool' acts as a mechanism that can lock a system to a certain resilience capacity preventing it from utilising other capacities of resilience. Based on this we suggest an expansion or revision of the capacities concept found in the resilience literature, allowing it to better describe severe shocks like the COVID-19 pandemic.
Keywords: 330